2010
DOI: 10.4314/thrb.v12i2.56401
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant activity of Vetiveria zizanioides root extract

Abstract: Free radicals induce numerous diseases by lipid peroxidation and DNA damage. It has been reported that some of the extracts from plants possess antioxidant properties capable of scavenging free radicals in vivo. Vetiveria zizanioides belonging to the family Gramineae, is a densely tufted grass which is widely used as a traditional plant for aromatherapy, to relieve stress, anxiety, nervous tension and insomnia. In this regard, the roots of V. zizanioides was extracted with ethanol and used for the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Polyphenols contribute directly to the antioxidant activity of medicinal plants (Abuajah et al. 2014; Subhadradevi et al., 2010). The quantification of polyphenols in the aqueous root extract of V. zizanioides by Folin Ciocalteu method substantiated the results of Devprakash and Subburaju (2011), where the fresh aqueous root extracts of V. zizanioides showed a polyphenol content of 15.43 ± 0.31 mg tannic acid equivalents per 100 g dry weight of sample.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols contribute directly to the antioxidant activity of medicinal plants (Abuajah et al. 2014; Subhadradevi et al., 2010). The quantification of polyphenols in the aqueous root extract of V. zizanioides by Folin Ciocalteu method substantiated the results of Devprakash and Subburaju (2011), where the fresh aqueous root extracts of V. zizanioides showed a polyphenol content of 15.43 ± 0.31 mg tannic acid equivalents per 100 g dry weight of sample.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Das et al, [23], the extracts from the roots of H. indicus inhibited the Ecoli growth, and it was found that the presence of bioactive compounds such as steroids, tannins, saponins, glycosides, flavonoids, and polyphenols might contribute to this antibacterial activity. Work conducted to investigate the effect of roots extracts of V. zizanioides implied that the presence of tannins can be the active compound responsible for antibacterial activity against E-coli bacteria [24].…”
Section: Discussionmentioning
confidence: 99%
“…The root of Sida cordifolia exhibited DPPH radical, reducing power, nitric oxide radical, hydrogen peroxide radical [45] , and ABTS radical [46] scavenging activities. The antioxidant activity of the Balarista can also be supported by the free radical scavenging property of Woodfordia fruticosa [47] , Alpinia galanga [48] , Elettaria cardamomum [49] , Syzygium aromaticum [50] , Ipomoea digitata [51] , Paederia foetida [52] , Ricinus communis [53] , Tribulus terrestris [54] , Vetiveria zizanioides [55] .…”
Section: Hptlc Analysismentioning
confidence: 99%